(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Information technology (IT) has generated a rapidly evolving terminology that poses unique challenges for translation. This article examines the linguistic characteristics of IT terminology and the strategies employed to translate IT terms across languages. Drawing on comparative analysis of English IT terms and their counterparts in languages like Uzbek, Russian, Spanish, Arabic, and others, the study classifies IT terms by structure and formation, and evaluates translation approaches such as direct borrowing, calque formation, and semantic adaptation. The results highlight the predominance of English as a source of IT vocabulary, with many languages borrowing terms wholesale to maintain international consistency. At the same time, language-specific efforts at localization (e.g. coining native terms or loan translations) demonstrate the tension between global uniformity and local linguistic identity. A notable finding is the ubiquity of abbreviations and acronyms in IT and their preservation in translation. The discussion situates these findings within translation theory, considering foreignizing vs. domesticating strategies, and emphasizes the need for terminological standardization to ensure clarity. This study contributes to translation studies and linguistics by detailing how IT terminology is managed across languages and what this implies for translators and terminology planners.